Drag-free control and technological risk assessment for the LISA gravitational wave space antenna - Roberts, P. (Cranfield University, 2000)
The quest for the direct detection and observation of gravitational waves remains one of the lasting scientific challenges of the 20th century, and one that will continue on into the 21 st. Concepts and technologies are being developed that will, early in the new millennium, allow their direct observation for the first time. This will be the beginning of the gravitational wave astronomy revolution. The LISA (Laser Interferometer Space Antenna) mISSIOn is one of the cornerstones of this revolution. Observing in the low-frequency band, it will provide information about our universe that cannot be gathered from the ground. This band contains sources fundamental to our understanding of how the universe began and operates. In turn, fundamental to the LISA mission is the concept of drag-free control. This provides the relatively undisturbed environment for the test-masses which form the references for the measurement of the gravitational waves. Without it the effect of gravitational waves would be but a whisper amongst a cacophony of disturbances. It is drag-free control for the LISA mission which forms the basis for the majority of this thesis. The research and development work carried out by the author has involved the development of a control model of the LISA dragfree control system to assess its feasibility. The author proposes a different approach to the problems involved from that suggested by other authors. It is shown that this approach, unlike those suggested in the mission baseline studies, fulfills the control requirements for the LISA mission. Technological risk assessment in general, as well as that associated with the LISA mission, is also considered.